The Impact of Multiple Risk Factors for Venous Thromboembolism and Its Implications for Management - Anil P. George MD; Paul Kent MD (SAGE Publishing, 2019)
Venous thromboembolism (VTE) is a rare multifactorial disorder in childhood with an annual incidence of about 0.07 to 0.14 per 10 000 children. A 15-year-old female with a body mass index of 48 kg/m 2 who endorsed oral contraceptive use presented with clinical findings consistent with deep venous thrombosis along with the presence of a pulmonary embolism. Further workup revealed that the patient was heterozygous for factor V Leiden and homozygous for prothrombin G20210A mutations. There are no current pediatric guidelines for the antithrombotic management of patients with multiple risk factors for VTE. Two such risk factors, obesity and the use of estrogen-containing hormone contraceptives, have been implicated in adult VTE cases but have not been clearly delineated in pediatric patients. The need for guidance regarding the VTE management of these patients has become more apparent given the increasing incidence of childhood obesity and the number of adolescents using oral contraceptives. Additionally, thrombophilia testing remains controversial though testing may be indicated in asymptomatic first-degree relatives and in families with antithrombin, protein C, or protein S deficiencies. Given the increased incidence of multiple risk factors for VTE, there is also a need to develop a comprehensive risk assessment tool for pediatric patients at high risk of VTE.